Salgado Paraense: an inventory of a forgotten coastal Amazonian avifauna - Lees, Alexander Charles; Thompson, Ian; Moura, Nárgila Gomes de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
We report on the poorly-known, coastal avifauna of the Salgado Paraense (in the state of Pará, Brazil) east of the delta of the Amazonas river, combining data from recent surveys with an analysis of historical records. Three-hundred and twenty three species were recorded in the habitats inventoried: estuarine, beach and mangrove habitats, restinga, seasonally-flooded grasslands and secondary forest. Particularly noteworthy records included: the discovery of a disjunct population of Laterallus jamaicensis; a previously unrecorded staging ground for Stercorarius spp.; the second documented Brazilian record of Calidris pugnax; the first documented records in Pará for a number of marine species, including the regionally-threatened Sterna dougallii, and the rediscovery of ‘Picumnus pallidus’, a taxon of uncertain validity, all documented by archived digital vouchers. Coastal habitats represent an important contribution to local avian species-richness in Amazonia and they are theoretically better-protected by existing conservation units than neighboring terra firme habitats, yet this region’s biodiversity remains threatened by habitat loss, hunting, and major infrastructure improvements.